In the moment with music: an exploration of the embodied and sensory experiences of people living with dementia during improvised music-making. Issue 11 (24th November 2022) - Dowlen, Robyn; Keady, John; Milligan, Christine; Swarbrick, Caroline; Ponsillo, Nick; Geddes, Lucy; Riley, Bob
Abstract: The term 'in the moment' has received growing interest in the context of music programmes for people living with dementia, with music therapists, family carers, health-care professionals and people living with dementia themselves reporting the value of framing musical experiences in the 'here and now'. Although this term is being used more frequently within the literature, there has yet to be a formal examination of such 'in the moment' musical experiences and how they might benefit a person living with dementia. We used a multiple-case study approach to develop a thematic framework of 'in the moment' musical experiences within the context of a music-making programme for people living with dementia. The research followed six people living with dementia and four family carers, and used video-observation and video-elicitation interviews to capture and analyse 'in the moment' experiences. Four thematic observations were developed which captured 'in the moment' musical experiences: Sharing a life story through music, Musical agency 'in the moment', Feeling connected 'in the moment' and Musical ripples into everyday life . These findings showcase the creativity and musical abilities of people living with dementia whilst affirming music as a medium to connect people living with dementia with their own life story, other people and the environments in which music-making takes place.